Theoretical Aspects of Creating a Scientific and Educational Platform for Information and Trading Systems - Glushchenko, Valery Vladimirovich; Inei, Yusubo Hissein Allafuza (Bumi Publikasi Nusantara, 2024)
The subject of the work is the theoretical aspects of creating a scientific and educational platform for information and trading systems; the object of the work is a scientific and educational platform for information and trading systems, the purpose of the work is to improve the efficiency of information and trading systems; to achieve this goal, the following tasks are solved: the concept of scientific support of information and trading systems is discussed; the paradigm of the development of scientific support for the design of information and trading systems is being formed; the methodological provisions and tasks of the general theory of scientific support of information and trading systems are described; the architecture of the scientific platform of information and trading systems is discussed; the scientific methods in the article are: system analysis, logical and historical analysis, philosophy and methodology of science, system engineering, theory of hierarchical systems; the scientific novelty of the article lies in the formation of a paradigm for the development of scientific support for design information and trading systems.